A Multidisciplinary Approach to Anesthetic Management of a Parturient with Severe Aortic Stenosis. (21st May 2015) - Tyagaraj, Kalpana; Gutman, David A.; Belliveau, Lynn; Sadiq, Adnan; Bhutada, Alok; Feierman, Dennis E.
Abstract : In order to optimize anesthetic management and avoid adverse maternal and fetal outcomes, a clear understanding of the changes in cardiovascular physiology that occur during pregnancy is paramount. The effects of normal gestation on the cardiovascular system are particularly significant in a parturient with cardiac valvular pathology. We present a case of a 27-year-old G2P0 at 37 weeks with a past medical history of diabetes, macrosomia, congenital bicuspid aortic valve with severe stenosis (valve area 0.7 cm 2 ) who was scheduled for elective C-section. A multidisciplinary discussion involving cardiologists, cardiac surgeons, obstetric surgeons, neonatal intensivists, perfusion staff, anesthesiologists, and nursing staff was held to formulate a plan for the perioperative management of this parturient. Also, contingency plans were formulated and discussed with the care providers, in the event of acute decompensation of the mother and baby and possible need for emergency aortic valvuloplasty and/or aortic valve replacement.